La jurisprudence de la Cour de justice de l’Union européenne sur les demandeurs d’asile LGBTI : une perspective queer postcoloniale - Ahmed Hamila (Genre, Sexualité et Société)
Decisions rendered by the Court of Justice of the European Union (CJEU) related to asylum on the basis of sexual orientation have mainly been analyzed by jurists. Thus, the scientific literature has especially discussed the legal foundations of these decisions, and their conformity with the law of the European Union or with international conventions. This article goes beyond this legal perceptive and analyzes the decisions of the CJEU by inserting them into a wider socio-political context. By adopting a critical approach that calls for a queer postcolonial epistemology, this research aims to relocate these legal decisions within their spatial and temporal context, which is characterized by homonationalism. Such a conceptual matrix sheds light on the power dynamics and disciplinary effects of the successive decisions of the CJEU on asylum seekers invoking persecutions based on their sexual orientation.